2018
DOI: 10.1097/md.0000000000012317
|View full text |Cite
|
Sign up to set email alerts
|

Association between the overexpression of Her3 and clinical pathology and prognosis of colorectal cancer

Abstract: Background:This study aimed to investigate the association between the overexpression of human epidermal growth factor receptor-3 (Her3) and the clinicopathological parameters and survival of patients with colorectal cancer (CRC).Methods:Relevant studies on the overexpression of Her3 (measured by immunohistochemistry) and overall survival (OS) in patients with CRC were searched for in PubMed, EMBASE, and Cochrane Library. Published data were extracted and computed into odds ratios (ORs) for assessing the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Typically, HER3, one member of EGFR family (EGFR, HER2, HER3, and HER4), plays a significant role in the formation of a heterodimer with EGFR on the surface of CRC cells, activating the intracellular signaling pathway when a ligand binds to the receptor [ 14 , 15 ]. The overexpression of HER3 in 30–80% of mCRC has been associated with the resistance to EGFR inhibitor [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, HER3, one member of EGFR family (EGFR, HER2, HER3, and HER4), plays a significant role in the formation of a heterodimer with EGFR on the surface of CRC cells, activating the intracellular signaling pathway when a ligand binds to the receptor [ 14 , 15 ]. The overexpression of HER3 in 30–80% of mCRC has been associated with the resistance to EGFR inhibitor [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The roles of HER3 in mediating cancer cell survival have been studied in different types of cancer such as breast, lung, and ovarian cancer 37,38 . In CRC, HER3 is expressed in ~ 75% of primary and metastatic tumors 39,40 , and HER3 overexpression is associated with poor prognoses in patients with CRC 41,42 . Because HER3 is a RTK protein with weak kinase activity and is considered as a "kinase-dead" receptor 43 , the canonical activation of HER3 in CRC and other cancer cells involves HER3 binding to its ligands and dimerizing with other proteins that have kinase activities.…”
Section: Discussionmentioning
confidence: 99%
“…cBioPortal analysis of TCGA and multiple other databases showed that majority of the tumors (>94%) do not carry mutation, duplication, or other alterations in HER3. Meanwhile, HER3 overexpression occurs frequently and is associated with poor prognosis in patients with CRC 46,47 . As a result, HER3 inhibition has been proposed as a promising targeted therapy strategy in different types of cancers.…”
Section: Discussionmentioning
confidence: 99%